2020
DOI: 10.3390/met10091180
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Powder-Bed Fusion Process Parameters on the Quality of as-Built IN718 Parts Using Response Surface Methodology

Abstract: Inconel 718 (IN718) is a nickel-based superalloy which is widely used in aerospace, oil, and gas industries due to its outstanding mechanical properties at high temperatures, corrosion, fatigue resistance, and excellent weldability. Selective laser melting (SLM), one of the most used powder-bed based methods, is being extensively used to fabricate functional IN718 components with high accuracy. The accuracy and the properties of the SLM fabricated IN718 parts highly depend on the process parameters employed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This can be attributed to the differences in the parameters of the LPBF process as also noted by Zhao et al and Yan et al [ 21 , 43 ]. It is well known that the process parameters of the LPBF process play a significant role in determining the properties of the as-built specimens as discussed extensively by Ravichander et al [ 8 , 12 ]. Additionally, the range of values defined by Gibson and Ashby was established for the mechanical properties of metallic foams.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the differences in the parameters of the LPBF process as also noted by Zhao et al and Yan et al [ 21 , 43 ]. It is well known that the process parameters of the LPBF process play a significant role in determining the properties of the as-built specimens as discussed extensively by Ravichander et al [ 8 , 12 ]. Additionally, the range of values defined by Gibson and Ashby was established for the mechanical properties of metallic foams.…”
Section: Resultsmentioning
confidence: 99%
“…The TPMS structures are used as shock absorbers in spacecrafts and high-speed trains due to their high energy absorption capabilities [ 5 , 6 ]. LPBF is one of the most widely used metal AM techniques to fabricate complex metal TPMS structures with high accuracy [ 7 , 8 , 9 , 10 , 11 ]. The LPBF is a layer-by-layer manufacturing process in which the laser beam selectively melts and joins the metal powder layers until the desired part is fabricated [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An EOS M290 metal 3D printer (EOS GmbH Electro Optical Systems, Germany) equipped with a 400 W Ytterbium fiber laser was used to fabricate the designed parts with three repetitions. The laser processing parameter set used for the fabrication were laser power (P) of 285 W, scanning speed (v) of 960 mm/s, hatch spacing (h) of 110 µ m, and layer thickness (t) of 40 µ m, with an energy density (E) of 67 J/mm3, as calculated from the Equation (1) [58][59][60]. A stripe scanning strategy with a 67° rotation angle in each consecutive layer was employed for all the parts.…”
Section: Powder Preparation and Fabricationmentioning
confidence: 99%
“…The experiment verified that an energy density level of 64.29 J/mm 3 better affected the microstructure, fractured surface, and cracking shape of the SP specimens. Ravichander et al [ 28 ] studied the 20 suggested sets of SLM process parameters ( P , s , and δ) in order to evaluate the dimensional accuracy, composition, and hardness corresponding to the interactions. The experiments tested a range of energy density values for the In718 superalloy needed to attain optimal values for each of the analyzed characteristics, and to enhance the fabrication quality of the as-built In718 specimens.…”
Section: Introductionmentioning
confidence: 99%